Medicines Use Reviews (MURs) : a case study in two community pharmacies - Latif, Asam (2012)
The Medicines Use Review and Prescription Intervention (MUR) service was commissioned as part of the 2005 community pharmacy contract for England and Wales. The aim of the MUR service is to improve patients’ knowledge and use of medicines and to reduce avoidable medicines waste. MURs form part of a Government strategy that aims to improve patients’ adherence to medicines in order to optimise health gain and reduce cost associated with unused medicines. MURs are also seen as a ‘concordance review’ and pharmacy’s professional bodies acknowledge the service as a means to further the professional role of community pharmacists. However, it remains uncertain from studies investigating the outcomes of MURs, the extent to which the service is benefitting patients. One significant drawback to previous studies is the lack of in-depth investigation of the MUR consultation and the patients’ perspective of the service.